2002
DOI: 10.1016/s0268-005x(01)00110-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Na+, K+ and Ca2+ on gels formed from fish mince containing a carrageenan or alginate

Abstract: The effects of mixtures of added chloride salts (0-1 % NaCl plus 0-1 % KCl plus 0-1 % CaCl 2) on the characteristics of blue whiting muscle gel containing different added gelation agent (iota-carrageenan, kappa-carrageenan, or sodium alginate) were studied by response surface methodology (RSM) and factor analysis (principal component analysis). The salts exhibited independent effects on gel properties. NaCl mainly altered breaking strength in the gels made with iota-carrageenan, the yellowness (b*) value in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…In many food formulations, starch and hydrocolloids are used with other ingredients, e.g., salts, as in the case of the mashed potatoes presented in this study, which contained potato starch and Na + from NaCl salt. Montero and Pérez-Mateos (2002) found that NaCl altered the breaking strength in gels made with ι-C and the yellowness (b*) value in gels made with κ-C. ι-C has no specific ion binding sites for monovalent ions, and bonds, therefore, arise only from electrostatic interactions (Picullel 1991). However, in the case of the κ-C, alkaline ions bind to the helix of the hydrocolloid, thus partially neutralizing the sulfate groups.…”
Section: Effect Of Cryoprotectant Addition and Freezing And Thawing Pmentioning
confidence: 99%
“…In many food formulations, starch and hydrocolloids are used with other ingredients, e.g., salts, as in the case of the mashed potatoes presented in this study, which contained potato starch and Na + from NaCl salt. Montero and Pérez-Mateos (2002) found that NaCl altered the breaking strength in gels made with ι-C and the yellowness (b*) value in gels made with κ-C. ι-C has no specific ion binding sites for monovalent ions, and bonds, therefore, arise only from electrostatic interactions (Picullel 1991). However, in the case of the κ-C, alkaline ions bind to the helix of the hydrocolloid, thus partially neutralizing the sulfate groups.…”
Section: Effect Of Cryoprotectant Addition and Freezing And Thawing Pmentioning
confidence: 99%
“…This difference is quite substantial in terms of folic acid since microgram quantities are required for the physiological functions in the human body. De Boisseson et al (2004) reported that sodium chloride strengthens intermolecular hydrophobic associations of the alkali chains which in turn lead to a decrease in the swelling ratio as well as porosity and an increase in elasticity in alginate capsules while Montero and Perez-Mateos (2002) reported that it increases gel strength, work of penetration and hardness. This is over and above the stability brought by ionic junctions.…”
Section: Evaluation Of Mechanical Properties Of Capsulesmentioning
confidence: 99%
“…In addition, Al-Remawi (2012) used sucrose as a crosslinking modifier for the preparation of calcium alginate films via external gelation and the prepared film was more uniform without the appearance of localized gelling areas at the surface. Moreover, monovalent cations (such as Na + and K + ) have also been used to adjust the external gelling properties of alginate (Goh, Heng, & Chan, 2012b;Montero & Perez-Mateos, 2002). For example, Goh, Heng, & Chan (2012b) reported that the added non-gelling Na + increased the tensile strength of the films crosslinked by Ca 2+ but it exerted the opposite effect on those crosslinked by Cu 2+ or Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%